2011
DOI: 10.1115/1.4002893
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Speciated Hydrocarbon Emissions and Flame Ionization Detector Response for Gasoline/Alcohol Blends

Abstract: The U.S. renewable ftiel standard has made it a requirement to increase the production of ethanol and advanced biofuels to 36 billion by 2022. Ethanol will be capped at 15 billion, which leaves 21 billion to come from other sources such as butanol. Butanol has a higher energy density and lower affinity for water than ethanol. Moreover, alcohol fueled engines in general have been shown to positively affect engine-out emissions of oxides of nitrogen and carbon monoxide compared with their gasoline fueled counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 9 publications
0
22
0
2
Order By: Relevance
“…The correction of the HC emission measurement of ethanol content fuels is out of the scope of this study. More details can be found elsewhere [15][16][17].…”
Section: Instruments -Legislation Requirementsmentioning
confidence: 99%
“…The correction of the HC emission measurement of ethanol content fuels is out of the scope of this study. More details can be found elsewhere [15][16][17].…”
Section: Instruments -Legislation Requirementsmentioning
confidence: 99%
“…Previous studies have pointed out a lack of selectivity of the heated FID towards oxygenated hydrocarbon compounds emitted in the exhaust from engines fuelled with high ethanol blended mixtures [28,29]. Therefore, the time-resolved THC volumetric concentration measured with the FID were corrected using the concentrations measured with the FTIR of ethanol, methanol, formaldehyde and acetaldehyde, and the FID response factor for each of them, as described by Clairotte et al [11].…”
Section: Analytical Instrumentationmentioning
confidence: 99%
“…Exhaust emissions were sampled 200 mm downstream of the of engine exhaust valve and fed via heated lines to a Horiba MEXA-9100EGR automotive gas analyser rack for measuring gaseous emissions, and to a Cambustion DMS500 differential mobility spectrometer to determine the number and size distribution of particulates in the exhaust. The Horiba analyser rack was fitted with a non-dispersive infrared absorption analyser for CO (±1 ppm) and CO2 (±0.01 %) measurement, a flame ionization detector for THC (±10 ppm) measurement (though it should be noted that no compensation was made the for presence of ethanol in the tested fuels; previous studies have shown that misinterpretation of FID measured THC levels can occur in fuels containing alcohols [28]), a magnetopneumatic analyser for oxygen (±0.1 %) measurement, and a chemiluminescence analyser to measure NOx (±1 ppm) concentrations in the exhaust gas. An IKA C1 bomb calorimeter was used to measure the higher heating values of the test fuels, from which the lower heating value for each was calculated.…”
Section: Methodsmentioning
confidence: 99%